Molecular Screen Identifies Cardiac Myosin–Binding Protein-C as a Protein Kinase G-Iα Substrate. (November 2015) - Thoonen, Robrecht; Giovanni, Shewit; Govindan, Suresh; Lee, Dong I.; Wang, Guang-Rong; Calamaras, Timothy D.; Takimoto, Eiki; Kass, David A.; Sadayappan, Sakthivel; Blanton, Robert M.
Abstract : Background—: Pharmacological activation of cGMP-dependent protein kinase G I (PKGI) has emerged as a therapeutic strategy for humans with heart failure. However, PKG-activating drugs have been limited by hypotension arising from PKG-induced vasodilation. PKGIα antiremodeling substrates specific to the myocardium might provide targets to circumvent this limitation, but currently remain poorly understood. Methods and Results—: We performed a screen for myocardial proteins interacting with the PKGIα leucine zipper (LZ)–binding domain to identify myocardial-specific PKGI antiremodeling substrates. Our screen identified cardiac myosin–binding protein-C (cMyBP-C), a cardiac myocyte–specific protein, which has been demonstrated to inhibit cardiac remodeling in the phosphorylated state, and when mutated leads to hypertrophic cardiomyopathy in humans. GST pulldowns and precipitations with cGMP-conjugated beads confirmed the PKGIα–cMyBP-C interaction in myocardial lysates. In vitro studies demonstrated that purified PKGIα phosphorylates the cMyBP-C M-domain at Ser-273, Ser-282, and Ser-302. cGMP induced cMyBP-C phosphorylation at these residues in COS cells transfected with PKGIα, but not in cells transfected with LZ mutant PKGIα, containing mutations to disrupt LZ substrate binding. In mice subjected to left ventricular pressure overload, PKGI activation with sildenafil increased cMyBP-C phosphorylation at Ser-273 compared with untreated mice. cGMP also induced cMyBP-C phosphorylation in isolated cardiac myocytes. Conclusions—: Taken together, these data support that PKGIα and cMyBP-C interact in the heart and that cMyBP-C is an anti remodeling PKGIα kinase substrate. This study provides the first identification of a myocardial-specific PKGIα LZ-dependent antiremodeling substrate and supports further exploration of PKGIα myocardial LZ substrates as potential therapeutic targets for heart failure.